2016
DOI: 10.1039/c5cy01798j
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the descriptor governing NO oxidation on mullite Sm(Y, Tb, Gd, Lu)Mn2O5for diesel exhaust cleaning

Abstract: Mn-based oxides Sm(Y, Tb, Gd, Lu)Mn2O5 are synthesized to identify a general descriptor that governs the catalytic performance in NO oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Polysulfones, produced through polycondensation, are known as high-performance materials with superior thermal, chemical, and mechanical properties, which represents an advantage for many applications, such as filtration membranes [28][29][30][31][32], coatings [33,34], composites [35][36][37], microelectronic devices [38], thin film technology [39], biomaterials [25,37,40], and fuel cells [41][42][43][44]. Introduction of functional groups into polysulfones solves some limitations, and also extends the range of potential applications of these high-performance materials through the specific properties gained, and thus provides wider scope.…”
Section: Synthesis and Characterization Of Polysulfones With Pendant mentioning
confidence: 99%
“…Polysulfones, produced through polycondensation, are known as high-performance materials with superior thermal, chemical, and mechanical properties, which represents an advantage for many applications, such as filtration membranes [28][29][30][31][32], coatings [33,34], composites [35][36][37], microelectronic devices [38], thin film technology [39], biomaterials [25,37,40], and fuel cells [41][42][43][44]. Introduction of functional groups into polysulfones solves some limitations, and also extends the range of potential applications of these high-performance materials through the specific properties gained, and thus provides wider scope.…”
Section: Synthesis and Characterization Of Polysulfones With Pendant mentioning
confidence: 99%
“…HT synthesis causes crystal growth at lower temperatures than the CP method, which results in high‐surface‐area materials desirable for heterogeneous catalysis and has been successfully used to prepare mullite oxides. [ 43,44,61–64 ] To synthesize AMn 2 O 5 , the metal salt precursors of A, Mn, and KMnO 4 are mixed in a molar ratio of 5:7:3 in DI water and then a precipitating agent (NaOH or KOH) is added dropwise. The HT treatment is conducted at 180–200 °C for 24–48 h in an autoclave under autogenous pressure.…”
Section: Mullite‐type Oxide Structure Synthesis and Stabilitymentioning
confidence: 99%
“…The HT treatment is conducted at 180–200 °C for 24–48 h in an autoclave under autogenous pressure. [ 43,44,61–64 ] The mullite oxide catalysts prepared by this method exhibit high specific surface area with narrow particle size distribution and well‐controlled morphologies. For example, Ma et al synthesized SmMn 2 O 5 with different morphologies such as nanorods and nanoparticles by varying the pH and HT reaction time.…”
Section: Mullite‐type Oxide Structure Synthesis and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct from the widely studied perovskite‐ and spinel‐type oxides, Mn‐based mullites with the general formula A″Mn 2 O 5 , whereas A″ is the trivalent rare‐earth metal ion, incorporate equivalent amount of Mn 3+ and Mn 4+ (i.e., Mn 3+ /Mn 4+ = 1) at square‐pyramidal and octahedral sites, respectively ( Figure a). Recent density functional theory (DFT) calculations identified that the d z2 orbital of Mn pyr 3+ (Figure b) largely overlapped with the O‐2p orbital of the adsorbed oxygen, and the strength of oxygen adsorption on the Mn pyr 3+ site was moderate, suggesting potentially favorable exchange kinetics of OH − by O 2 which was considered to limit ORR kinetics on metal oxides. [4a,10] Besides, the mullite SmMn 2 O 5 micropowder has exhibited acceptable ORR activity .…”
mentioning
confidence: 99%